Hopper discharge of cohesive powders using pulsated airflow. Issue 7 (1st May 2020) - Zhu, Lizhuo; Lu, Haifeng; Poletto, Massimo; Liu, Haifeng; Deng, Zhiwen
Abstract: An aerated hopper with pulsated aeration was designed to study the effect of square‐wave pulsated airflow on the discharge characteristics of cohesive and non‐cohesive powders. Experiments were carried out with pulsation frequencies between 0 (continuous) and 50 Hz. Two flow patterns were observed at different aeration rates and pulsation frequencies: intermittent and smooth. For non‐cohesive powders, pulsated aeration has a worsening effect on discharge flow. For cohesive powders, results revealed that pulsated aeration can reduce the minimum aeration necessary to allow continuous discharge. And the maximum discharge rate that can be attained applying pulsated aeration is higher than that of continuous aeration and it is significantly more uniform. The aggregates size of the powder was estimated and used to understand the stabilizing mechanism of pulsated aeration on the aggregative discharge. The model value of the minimum aeration rate and the discharge rate were obtained and compared with the experimental values.